IMPROVING TAX ADMINISTRATION IN THE ENTREPRENEURIAL ENVIRONMENT (World Economics and Finance Bulletin, 2026)
This article examines the improvement of tax administration in the entrepreneurial environment from theoretical, institutional, and practical perspectives. In modern economies, tax administration is not limited to the collection of budget revenues; it also functions as an institutional mechanism that influences business activity, voluntary tax compliance, transparency, formalization of economic operations, and the reduction of administrative costs for entrepreneurs